2014
DOI: 10.1097/opx.0000000000000319
|View full text |Cite
|
Sign up to set email alerts
|

Multifocal Pupillography in Early Age-Related Macular Degeneration

Abstract: The mean effect of AMD on contraction amplitudes and response delays reflected the severity of disease, and the NewStimuli protocol achieved good diagnostic accuracy across all AMD severity groups. Multifocal pupillographic objective perimetry may potentially be a useful method in monitoring progression of AMD and assessing change in retinal function with novel interventions in early AMD. Longitudinal studies are required to identify biomarkers that predict eyes at risk of progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 32 publications
0
40
0
Order By: Relevance
“…Figure 1C,D are from a study of eyes with a range of severities of AMD from early to late stage Exudative (Wet) AMD. The two figures illustrate the general findings of our mfPOP studies of retinal disease256912, (1) earlier stage disease displays a mix of hypo- and hyper-sensitive regions, (2) these later give way to concentrated sensitivity loss, (3) eyes with no hypersensitive regions respond poorly to treatment6. Mildly hypersensitive regions appear to be more common when AMD patients are tested with mfPOP at photopic rather than at scotopic levels7.…”
mentioning
confidence: 72%
See 2 more Smart Citations
“…Figure 1C,D are from a study of eyes with a range of severities of AMD from early to late stage Exudative (Wet) AMD. The two figures illustrate the general findings of our mfPOP studies of retinal disease256912, (1) earlier stage disease displays a mix of hypo- and hyper-sensitive regions, (2) these later give way to concentrated sensitivity loss, (3) eyes with no hypersensitive regions respond poorly to treatment6. Mildly hypersensitive regions appear to be more common when AMD patients are tested with mfPOP at photopic rather than at scotopic levels7.…”
mentioning
confidence: 72%
“…Since 2009 our group has published several reports using multifocal pupillographic objective perimetry (mfPOP)123456789101112. The method was pioneered by others1314.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Relatively recent advances in the understanding of the neural mechanisms that mediate the pupil response have greatly renewed interest in pupillometry as a tool for assessing retinal function in patients with acquired91011 and inherited12131415 retinal disease. That is, the afferent limb of the pupillary response to light is now thought to be driven primarily by intrinsically photosensitive retinal ganglion cells (ipRGCs) that contain the photopigment melanopsin1617.…”
mentioning
confidence: 99%
“…Using multifocal pupillography, Sabeti et al (2014) found reduced pupil responses in patients with early AMD, however their pupil paradigm is not designed to measure ipRGC function. While outer retinal deficits may have been manifest in the patients with early AMD, our testing conditions were primarily aimed towards optimum ipRGC isolation.…”
Section: 6mentioning
confidence: 99%